Angular‐ and polarization‐independent structural colors based on 1D photonic crystals. Issue 3 (May 2015) - Lee, Kyu‐Tae; Ji, Chengang; Banerjee, Debasish; Guo, L. Jay
<x xml:space="preserve">Abstract</x> A 1D photonic crystal‐based structural reflective color with angle‐invariant, polarization‐independent, and high‐purity characteristics is presented. Our proposed device is capable of creating a distinctive color that is insensitive with respect to the angle of incidence up to ±70° regardless of the polarization state of incident light. The presented approach can open the door to numerous applications, such as colored display technologies and imaging sensors.